Leadership and conditional cooperation in public good games: What difference does the game make? - Edward J. Cartwright; Denise Lovett (University of Kent, School of Economics, 2013)
We investigate experimentally whether the extent of conditional cooperation in public good games depends on the marginal return to the public good and type of game. The marginal return is varied from 0.2 to 0.4 to 0.8. The 'standard' game, in which three players contribute before a follower, is compared with a leader-follower game, in which one player leads and three follow. We find no strong evidence that the marginal return or type of game makes a difference to the extent of conditional cooperation. We also find no evidence that the type of game makes a difference to unconditional contributions. The level of marginal return does, however, have a strong effect on unconditional contributions. Our results highlight the critical role that can be played by leaders in a public good game.
Keywords: C72; H41; 330; Public good; conditional cooperation; reciprocity; leadership